Identification of conditions which lead to unjustified requests for emergency treatment of hypertensive patients - Suad Sivić; Larisa Gavran; Salih Tandir; Elvir Peštalić (Medicinski glasnik, 2017)
Aim: To determine most common factors making patients with high blood pressure seek professionally unacceptable treatment of hypertension at the Emergency Department. Methods: The survey was conducted at the Emergency Department of the Primary Health Care in Gradačac on randomly selected 207 patients who requested medical help because of high blood pressure. For all patients arterial blood pressure and body mass index (BMI) were measured. A survey about knowledge and attitudes regarding habits that affect high blood pressure as well as the socioeconomic conditions was made. Results: Prevalence of 10.3% was found with regard to visits to emergency care by patients due to high blood pressure. Most patients, 127(61.4 %), were overweight and 36(17.4%) were obese. Patients who rarely controlled their blood pressure were more frequent visitors of emergency medical services. Stressful situation occurs as a factor in a variety of forms. The survey showed that 76 (36.7%) patients sought medical help even though they had no blood pressure values that required emergency care. Conclusion: Poorly organized health care system with no continuous and comprehensive preventive promotional programs caused by inappropriate use of resources in health care. The reorganization of primary care with full implementation of family medicine and greater integration of family medicine with other levels of the health care system should provide a better control and treatment of other diseases such as hypertension.
Keywords: Emergency Department; hypertension; health services needs and demand